Flat currents in the classical AdS(5) x S-5 pure spinor superstring - Vallilo, B. C. (Int School Advanced Studies, 2004)
It is proven that the classical pure spinor superstring in an AdS(5) X S-5 background has a flat current depending on a continuous parameter. This generalizes the recent result of Bena, et at. for the classical Green-Schwarz superstring.
Keywords: superstrings and heterotic strings; AdS-CFT and dS-CFT correspondence